The Methodical Project About the Study of A.P. Gaidar’s Story «The School» in the 7th Middle School Grades (Филологический класс, 2015)
The way of the consideration of A. P. Gaidar's novel «The School» in 7th middle school grades is proposed. It is based on the acquiring of moral potential of the novel. The author suggests the approach that starts with a panel game lesson and gradually moves to seminar-like cogitative discussion. The author suggests, that such approach resembles the main novel character Boris coming-of-age.